Expanding PM-JAY to Senior Citizens: A Progressive Step Towards Holistic Health Coverage - Kulkarni, Annarao; Joshi, Krupal J (Indian Journal of Community Health, 2025)
India’s healthcare landscape is witnessing a significant shift with the recent inclusion of senior citizens under the Pradhan Mantri Jan Arogya Yojana (PM-JAY), the government’s flagship health insurance scheme. This expansion is a commendable move toward providing equitable healthcare, recognizing the unique needs of the elderly population, and aligning the country’s healthcare policy with international standards where senior citizens receive universal health protection. For a rapidly aging population, this extension comes as a beacon of hope, marking a major step forward in safeguarding the health of the most vulnerable in society.